Prescription Pattern Monitoring and Off-label Use of Medicines in the Pediatric Department at Tertiary Care Teaching Hospital - Pandey, S.; Yadav, C. K.; Ghimire, P.; Shrestha, A. C. (Kathmandu University Medical Journal, 2020)
Background Off-label use means the use, concerning dosage, indication, route of administration, or age, of pharmaceutical products which are beyond the terms of the product license. For regulatory bodies and physicians, the global challenge is to achieve optimum pediatric drug therapy. Objective This prospective observational work was carried out in the paediatric department to evaluate the prescribing pattern of medicines and to identify the use of off-label drugs. Method A cross-sectional study was carried in 200 paediatric patients of ages between 0 and 12 years at the paediatric outpatient department of Universal College of Medical Sciences, Bhairahawa. Data were collected by reviewing the prescription paper and the required information was recorded using a structured data collection sheet prepared for study. The prescribing pattern was assessed by using the World Health Organization (WHO) Prescription Indicators and off-label use was assessed using the WHO Children Formulary 2010. Result Among 413 total prescriptions, only 5.56% of drugs were found to be prescribed by generic name, 16.7% of prescriptions were found to be antibiotic and 57.62% of prescribed drugs were from essential drug list. Out of 413 prescribed drugs, 16.46% of drugs were found to be off-label. The maximum extent of off-label prescribing was 51.47% in the child, followed by infants (42.6%) and neonates (5.8%). Fexofenadine; antihistaminic (23.56%), Amoxicillin+clavulanic acid; antibiotic (22.06%) had higher off-label use. Off-label dose (71.8%) was the most common cause of off-label prescribing. Conclusion Off-label prescribing among pediatric patients is common. More eminence data on the safety and efficacy of off-label medicines must be generated to rationalize paediatric pharmacotherapy.